ANALISIS TEKNIK DAN IDEOLOGI TERJEMAHAN PADA NOVEL LEAP OF FAITH OLER DANIELLE STEEL DAN PURI KENAN GAN OLEH KATHLEEN S. W. - Edward, Edward (Jurnal Ilmu Budaya, 2014)
This is a research about an analysis of technique and ideology of translating of Leap of Faith by Danielle Steel and Puri Kenangan byKathleen.S. W The aims of this research are to identify the translation techniques applied by the translator in translating the novel and to analyze the translation ideology. The method in this study is descriptive qualitative using content analysis approach. The source of the data was taken from the English version novel "Leap of Faith "by Danielle and the translated version "Puri Kenangan "by Kathleen S. W The result of this research shows that there are 4 translation techniques applied by the translator, that is, borrowing, naturalization borrowing, calque, literal, transposition, compensation or substitution, modulation, amplification, description, particularization, adaptation, established equivalence, discursive creation and linguistic compression. The translation ideology tends to keep foreignization with a tendency to maintain language or cultural characteristics of the source language.